Comparison of alternative roundwood pricing systems – a simulation approach - Malinen, Jukka; Haring, Mika; Kilpeläinen, Harri; Verkasalo, Erkki (Silva Fennica, 2015)
In a closed market, roundwood buyers pricing system affect the roundwood flow from the stands to different roundwood users. If a buyer is capable to discriminate higher value stands from low quality stands better than its competitors, the buyer should be able to buy better raw material. In the study, a discrete event simulation was used to examine the effect of residual value appraisal (RVA) -based pricing of roundwood by log dimensions and grades compared to the traditional pricing based on average unit prices (UP) of roundwood assortments on roundwood flow. The core of the simulation model was the data containing 51 pine dominated stands from southern Finland. Sample trees were theoretically bucked by the bucking simulator in order to estimate the volumes, dimensions and grades of the logs and roundwood assortments. The simulation model of roundwood markets included four roundwood buyers, two corporations and two saw milling enterprises. The main finding of the study was that the buyers who use RVA gains an advantage and receives better quality compared to buyers who use UP. As the number of buyers using RVA increases, the competition increased and the advantage decreased.